Design and MATLAB Simulation of a Composite PID Controller for EPS Test-Benches - Mai, Yun Fei; Liu, Shao Long; Ding, Wen Jing (Applied Mechanics and Materials, 2014)
For the problems that exist in EPS composite test-benches, PID control laws are expounded, a composite PID controller is designed, which is integrated with multiple advanced PID control algorithms (variable-integral PID algorithm, PID algorithm with filters, partial derivative PID algorithm, PID algorithm with dead zone), and it is simulated by MATLAB. The simulation results show that the improvement of accuracy and the impacts mitigation of the nonlinearity and external electromagnetic interferences are achieved well through the composite PID controller, and there is practical significance.